Accidental Acute Poisoning of two Children by Paracetamol-Codeine (1000 Mg/60 Mg) Association - A Case Report - Diallo, A; Eliassou, M; Djadou, K; Potchoo, Y; Creppy, EE (Global Journal of Medical and Clinical Case Reports, 2016)
<span style="color: #222222; font-family: Roboto, serif; font-size: 15px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Paracetamol is one of the most used drugs in the world. We report here two cases of children poisoning (less than 3 years old) who were accidentally administered an adult form of rectal suppository containing a combination of paracetamol-codeine (1000 mg/60 mg). The first child received a dose of 154 mg /kg of paracetamol and 9 mg/kg of codeine two times daily for 2 days. Clinical signs were vomiting and epigastric abdominal pains. Biochemistry showed an increase of liver enzymes (4 to 40 fold), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma glutamyl transpeptidase (GGT). The second child received the suppositories discontinuously (two times daily) and showed less severe signs of intoxication. The administration of N-acetylcysteine at admission into hospital limited the toxic effects of paracetamol. The toxic effects of codeine, such as central nervous system (CNS) depression were not obvious in both cases.